PENGARUH MINYAK ATSIRI DAUN JERUK PURUT (Citrus hystrix) TERHADAP DINDING SEL BAKTERI Staphylococcus aureus - Opstaria Saptarini; Ismi Rahmawati (Research Center for Biology-Indonesian Institute of Sciences, 2021)
Kaffir lime leaves essential oil has activity to inhibit bacterial growth. The mechanism of the inhibition is thought to be located in thebacterial cell wall. This study aimed to determine the antibacterial work location of kaffir lime leaf essential oil against Staphylococcus aureus ATCC 25923. Kaffir lime leaves were distilled by steam distillation, essential oils obtained were identified by organoleptic quality, evaporation, solubility in alcohol, refractive index and specific gravity. The results were compared under with the literature. The results of essential oils were made with various concentrations of 100, 50, 25, 12.5, 6.25, 3.13, 1.56, 0.73, 0.39, and 0.20%. The results of the concentration series were tested for antibacterial activity with the macrodilution method followed by the determination for the location of bacterial growth inhibition using the Scanning Electron Microscope (SEM). The yield of kaffir lime leaf essential oil was 0.82%. The observation of organoleptic essential oil has a light yellow color, the distinctive odor of kaffir lime, a liquid form, and distinctive lime taste. Refractive index examination resulted 1.454; specific gravity 0.8317, and soluble in 70% ethanol with a ratio of 1:1. The Minimum BactericidalConcentration (MBC) obtained from the antibacterial activity test was 6.25%. Kaffir lime leaves essential oil mechanism occurred in the cell walls and cell membranes of Staphylococcus aureus.